Does apelin-13 affect the development of brown fat? - Yilmaz, U.; Erden, Y.; Tekin, S.; Etem, E.; Sandal, S. (Wiley-Blackwell, 2014)
[Abstract Not Available]
Keywords: Apelin; UCP1; white adipose tissue; brown adipose tissue